YIELD AND PROFITABILITY OF DRUM SEEDED RABI RICE AS INFLUENCED BY NITROGEN LEVELS AND WEED MANAGEMENT PRACTICES - D. SAIDA NAIK; M. YAKADRI, K. PREETHIKA, K. P. VANI, M. MADHAVI, G. JAYASREE (The Journal of Research, PJTSAU, 2023)
A field experiment was conducted at College Farm, Agricultural College, Rajendranagar, Hyderabad during Rabi 2020-21 and 2021-22 to study effect of nitrogen levels and weed management practices of drum seeded rice. Field trial consisted of 16 treatments having four weed management practices and four nitrogen levels laid out in factorial randomized block design. Pretilachlor 6 % + Pyrazosulfuron-ethyl 0.15 % GR 615 g ha-1 as PE fb mechanical weeding at 25 and 50 DAS (W4) has yielded significantly higher grain and straw yield followed by Pretilachlor 6 % + Pyrazosulfuron-ethyl 0.15 % GR 615 g ha-1 as PE fb Penoxsulam 1.02 % + Cyhalofop butyl 5.1 % OD 120 g ha-1 as POE (W2). Regarding economics, W2 had resulted in higher B C ratio followed by W4. Among the nitrogen levels, 125 % RDN (N4) had higher yield and B.C.R statistically comparable with 100 % RDN (N3). Interaction of W4N4 had attained higher yield while the economics gained was highest with W2N4.